Deferoxamine may enhance 5-aminolevulinic acid-based fluorescence in glioma surgery - Yano, Hirohito; Shinoda, Jun; Iwama, Toru (Translational Cancer Research, 2017)
Glioblastoma multiforme (GBM) is one of the most malignant brain tumors, because of its proliferative and invasive characteristics. The median survival is 12−16 months, despite multidisciplinary therapies, including surgery, radiation, and chemotherapy (1,2). GBM tumor cells migrate into the brain parenchyma far from the tumor mass and recurrence is common along the periphery of the tumor removal cavity, even in cases where the enhanced lesion has completely disappeared postoperatively (2). However, it is difficult to evaluate tumor spread of GBM on magnetic resonance imaging (MRI). We have previously reported a positron emission tomography (PET) study in which we compared the methionine (MET) uptake area to the area of gadolinium (Gd) enhancement on MRI in patients with GBM (3). We showed that the MET uptake area completely enveloped the Gd-enhanced area. In most cases, the MET uptake area enclosed the outer region of the Gd-enhanced area, with an additional 30 mm expansion. In contrast, the Gd-enhanced area coincided with only 58.6% of the MET-uptake area on average. Based on these results, we identified three cases of possible GBM recurrences after complete resection; they presented as new Gd-enhanced lesions in the MET uptake area at the edge of the surgical removal cavity (3). Hence, MET-PET may be useful for predicting local recurrence, given the metabolic abnormalities in residual tumor cells even before local tumor recurrence could be discerned on MRI (4).